PSYCHOLOGICAL AND LINGUISTIC FOUNDATIONS OF FOREIGN LANGUAGE TEACHING IN LIFELONG LEARNING - Ne'matillayeva Mohlaroy Uluģbek qizi (European Science Publishing, 2025)
This article thoroughly examines the psychological and linguistic foundations of teaching foreign languages within the lifelong learning system. It analyzes psycholinguistic approaches, motivation, age-related factors, cognitive strategies, and language competence development. Emphasis is placed on the interrelation between educational stages and language acquisition efficiency. The article concludes with practical recommendations to improve language teaching methodology across the continuum of education.
Keywords: Lifelong learning, foreign language teaching, psycholinguistics, motivation, age factor, cognitive strategies, language competence, communicative approach, linguistic foundations, educational psychology.